2004
DOI: 10.1037/0735-7036.118.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Direct Social Contacts Override Auditory Information in the Song-Learning Process in Starlings (Sturnus vulgaris).

Abstract: Social influence on song acquisition was studied in 3 groups of young European starlings raised under different social conditions but with the same auditory experience of adult song. Attentional focusing on preferred partners appears the most likely explanation for differences found in song acquisition in relation to experience, sex, and song categories. Thus, pair-isolated birds learned from each other and not from broadcast live songs, females did not learn from the adult male tutors, and sharing occurred mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
85
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 53 publications
10
85
0
Order By: Relevance
“…Social experience per se can evidently have as much influence on the development of the primary auditory area as the sensory experience in the experiment by Poirier et al (2004). Thus, both the birds raised in pairs or solitarily showed as many abnormalities (lack of neuronal selectivity) as the sensory deprived birds.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Social experience per se can evidently have as much influence on the development of the primary auditory area as the sensory experience in the experiment by Poirier et al (2004). Thus, both the birds raised in pairs or solitarily showed as many abnormalities (lack of neuronal selectivity) as the sensory deprived birds.…”
Section: Resultsmentioning
confidence: 93%
“…Warbling develops progressively from subsong in the course of the bird's first year of life, whereas whistles appear suddenly during the first winter around 9 month of age (AdretHausberger, 1989). Moreover, young birds raised without direct contact with adults will not develop whistles but will produce warbling song (Poirier et al, 2004;Bertin et al, 2007). Finally, neuroethological as well as functional magnetic resonance imaging (fMRI) studies performed on starlings revealed that these two distinct categories of song are not processed in the same way in the brain De Groof et al, 2013).…”
Section: Testing Turn Taking In An Animal Model: the Starlingmentioning
confidence: 99%
See 3 more Smart Citations